THE IMPACT OF THE CENTRAL BANK REFINANCING INSTRUMENT ON THE MONEY MARKET (EVIDENCE FROM UZBEKISTAN) (World Economics and Finance Bulletin, 2022)
This article is devoted to the consideration of the emergence of the refinancing instrument of central banks. In addition, it analyzes significance and the stages of the impact of this instrument on the economy in reliance upon the research conducted by scholars and statistical data in the case of Uzbekistan. According to the results of the analysis, this instrument was widely used to curb inflation in the 1990s. However, as a drawback, it has hindered the development of the private sector through the “compression effect”. Moreover, the fact that the Central Bank of Uzbekistan did not use a negative base rate of interest in practice and the fact that inflation was low, did not promote any economic growth. Herewith, the article investigates the impact of the central banks’ refinancing instrument on interest rates in the money market. According to the results of the analysis, until 2017, the impact of this instrument on the money market interest rate was insignificant, but since 2017, the impact of the refinancing instrument on the money market has been increasing.
Keywords: Monetary policy; inflation; money market; money supply